Revision of the genus Seminemacheilus, with the description of three new species (Teleostei: Nemacheilidae) - Yoğurtçuoğlu, Baran; Kaya, Cüneyt; Geiger, Matthias F.; Freyhof, Jörg (Zootaxa, 2020)
The nemacheilid genus Seminemacheilus is revised. Six species are recognised, three of them described herein as new. All species are endemic to Central Anatolia. Seminemacheilus lendlii from the Sakarya River drainage and the endorheic Lake Aksehir and Eber basins, S. ispartensis from Lake Eğirdir basin and S. ahmeti from Sultan Sazlığı are valid species. Although Seminemacheilus lendlii and S. ispartensis have almost identical COI sequences, they are distinguished by the shape of the caudal peduncle and the presence of scales on the caudal peduncle in S. ispartensis (vs. absent in S. lendlii). Seminemacheilus attalicus, new species, from Kırkgöz drainage, is distinguished by having a slightly emarginated caudal fin, a central pore in the supratemporal canal and a marbled flank pattern. Seminemacheilus ekmekciae, new species, from Lake Tuz basin is distinguished by having a roundish caudal fin, a short post-dorsal length and large brown blotches fused into stripes on the flank. Seminemacheilus tubae, new species, from Lake Beyşehir basin, is distinguished by having a truncate caudal fin and 2–5 (6) supraorbital head pores. Seminemacheilus dursunavsari from the Göksu River drainage is not a valid name and this population is identified as S. tubae.